Young People's Pre-Conceptions of the Interactions between Climate Change and Soils – Looking at a Physical Geography Topic from a Climate Change Education Perspective. Issue 2 (4th March 2022) - Deisenrieder, Veronika; Müller, Svenja; Knoflach, Bettina; Oberrauch, Anna; Geitner, Clemens; Keller, Lars; Stötter, Johann
Abstract: The interactions of climate change and soils (ICCS) are scarcely examined in Climate Change Education (CCE). Analyzing the pre-conceptions of secondary school students ( n = 421 ) reveals a high number of missing answers (48.2%), while residual participants responded with either medium (33.3%) or low (11.5%) complexity levels. The natural and the human sphere are scarcely interconnected and mentioned positive feedback effects indicate students' spatial distance to the ICCS that occur in Alpine regions. In order to bridge these gaps with more elaborated and regional concepts, a careful consideration of ICCS content is urgently recommended for CCE.